Analisis Penggunaan Bahasa Indonesia dalam Dakwah Ustad Hanan Attaki - Bintang Astian Hamzah; Muhamad Faizudin (Mutiara Pendidikan dan Olahraga, 2024)
Indonesian has an important position and function for the Indonesian nation in the territory of the Unitary State of the Republic of Indonesia (NKRI). Indonesian has become the national language since the agreement was stipulated in the Youth Pledge on October 28 1928, functioning as a symbol of pride, a symbol of identity, a means of unification and a means of communication. The position and function of Indonesian in religion, namely as a link between spoken and written languages, was emphasized by the Islamic religious figure "Ustad Hanan Attaki" making Indonesian the main language to be able to integrate various parent languages ​​in different religious contexts, and as a means of integrating and convey religious messages in the diversity of religions in Indonesia. Indonesian is widely used in various religious activities, for example da'wah, as well as religious literature such as translations of the Koran. Indonesian continues to play a dominant role in supporting communication and religious education that is comprehensive and can be accessed by all communities. This shows how Indonesian functions as a cultural and spiritual bridge, strengthening social connections in a multi-religious society. This research aims to analyze the use of Indonesian spoken by Ustad Hanan Attaki in his lectures, what he analyzes is the language style and method of delivery. The research method used was a qualitative descriptive method using data collection techniques that were found to be based on Ustad Hanan Attaki's lectures.